222k views
4 votes
What is this answer? 3(2x+ 1) + X= -39

1 Answer

2 votes

Answer:

x = 6

Explanation:

3 (2 x + 1) + x = -39

3 (2 x + 1) = 6 x + 3:

6 x + 3 + x = -39

Grouping like terms, 6 x + x + 3 = (6 x + x) + 3:

(6 x + x) + 3 = -39

6 x + x = 7 x:

7 x + 3 = -39

Subtract 3 from both sides:

7 x + (3 - 3) = -3 - 39

3 - 3 = 0:

7 x = -3 - 39

-3 - 39 = -42:

7 x = -42

Divide both sides of 7 x = -42 by 7:

(7 x)/7 = (-42)/7

7/7 = 1:

x = (-42)/7

The gcd of -42 and 7 is 7, so (-42)/7 = (7 (-6))/(7×1) = 7/7×-6 = -6:

Answer: x = -6

User Turamarth
by
4.9k points